2019
DOI: 10.1097/md.0000000000014852
|View full text |Cite
|
Sign up to set email alerts
|

Effect of statins on Parkinson's disease

Abstract: Background: Statins have key lipid-lowering, anti-inflammatory, and anti-oxidative effects. However, it remains unclear whether statins are beneficial to patients with Parkinson's disease (PD). This study aimed to evaluate the relationship between statins and PD through a systematic review. Methods: This study adhered to the guideline of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Potentially relevant case-control or cohort studies publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 20 publications
1
21
1
Order By: Relevance
“…This study investigated the association between statin therapies and their non‐canonical neurologically relevant mechanisms of action and their efficacy of risk reduction across multiple age‐related NDD. Results reported herein are consistent with previously published outcomes for statin therapy and a single NDD 7,10–14,20,21,25,27,28,31–36,49 thereby validating our findings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study investigated the association between statin therapies and their non‐canonical neurologically relevant mechanisms of action and their efficacy of risk reduction across multiple age‐related NDD. Results reported herein are consistent with previously published outcomes for statin therapy and a single NDD 7,10–14,20,21,25,27,28,31–36,49 thereby validating our findings.…”
Section: Discussionsupporting
confidence: 93%
“…Multiple studies report an association between statin use and AD, 10–13,20 dementia, 7,21,25,26 MS, 27,28 PD, 29,30 and ALS 31,32 . Current meta‐analyses for AD, 21,33 dementia, 21 MS, 34 PD, 35 and ALS 36 suggest that statin use is associated with NDD risk decrements, except for ALS—as the evidence is insufficient to draw any conclusion—and all call for the addition of further studies to add to the existent literature.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta‐analysis comprised 10 published studies confirmed the protective effects of statins against the development of PD 56 . Similarly, a systematic review and meta‐analysis comprised 17 published studies demonstrated that statin users mainly atorvastatin reduce PD risk 57 . These systematic review and meta‐analysis studies had some limitations including the results were obtained from observational studies, which are susceptible to various biases, selective, information, confounding, and follow‐up biases were unavailable in the cohort and case–control studies, the methods used to diagnose PD varied among the included studies, and most cases were diagnosed using medical records.…”
Section: Protective Role Of Statins In Pdmentioning
confidence: 88%
“…56 Similarly, a systematic review and meta-analysis comprised 17 published studies demonstrated that statin users mainly atorvastatin reduce PD risk. 57 These systematic review and meta-analysis studies had some Study type Findings Ref.…”
Section: Protec Tive Role Of S Tatin S In Pdmentioning
confidence: 99%
“…However, the same was not observed between lovastatin users, which did not show a risk of PD decrease (Wolozin et al, 2007). A meta-analysis involving nine cohort and eight case-control studies has also suggested that statins (especially atorvastatin) could reduce the risk of PD (Yan et al, 2019). On the other hand, some studies showed that high levels of LDL cholesterol and triglycerides could be protective factors against PD (Fu et al, 2020;Rozani et al, 2018).…”
Section: -Hydroxy-3-methyl-glutaryl-coenzyme a (Hmg-coa) Reductase In...mentioning
confidence: 94%